2013
DOI: 10.4103/0975-7406.114317
|View full text |Cite
|
Sign up to set email alerts
|

Scalpel versus electrosurgery: Comparison of gingival perfusion status using ultrasound Doppler flowmetry

Abstract: The main prerequisites of any surgical procedure are achievement of good visibility and access to the site with minimal bleeding and rapid and painless healing. With the advancement of technology the armamentarium for oral surgical procedures has also widened. The use of alternate methods to the traditional scalpel such as electrosurgery, laser, and chemicals has been widely experimented with. This article aims to report the gingival perfusion pre-operatively and post-operatively, comparing the use of scalpel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Manivannan et al [36] reported that scalpel caused more bleeding at the operative site when compared to electrosurgery. However, less damage to adjacent tissues and faster wound healing was observed with scalpel.…”
Section: Accepted Manuscriptmentioning
confidence: 98%
See 1 more Smart Citation
“…Manivannan et al [36] reported that scalpel caused more bleeding at the operative site when compared to electrosurgery. However, less damage to adjacent tissues and faster wound healing was observed with scalpel.…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…[2,28,31,35,36] Liboon et al [2] examined the histologic effects of scalpel, CO2 laser, and electrosurgical incisions on the mucosal tissue in pigs. They suggested that tissue damage was lower with scalpel, while electrosurgery and CO2 laser provided better hemostasis.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Manivannan et al . [ 21 ] attributed this delay in wound healing to decreased blood flow by the 7 th day in electrosurgically treated areas. They also stated that wound healing is influenced by revascularization rate, preservation and reconstruction of microvasculature.…”
Section: Discussionmentioning
confidence: 99%
“…Gingivectomy (Scalpel) procedure is an effective form of treatment when indicated as the procedure is technically simple, accurate and causes less damage to adjacent tissue [7,8]. Perioperative hemorrhage is the main disadvantage of Scalpel excision.…”
Section: Discussionmentioning
confidence: 99%